Akutní intersticiální nefritida s uveitidou u dĕtí a mladistvých - Janda, J; Rambousek, V; Kolský, A; Stejskal, J; Klimesová, D; Feber, J (Ceskoslovenska pediatrie, 1990)
Acute non-suppurative tubulointerstitial nephritis was recorded within a five-month interval in 1988 in one girl and two boys aged 15, 16 and 12 years. The common feature was non-selective proteinuria, slight glycosuria, anaemia, a sedimentation rate of more than 100 mm/2 hrs hyperatotaemia not calling for dialyzation treatment (268, 354 and 266 mumol/l plasma creatinine resp.), a markedly impaired concentrating capacity (540, 593 and 520 mOsm/kg urine resp.). In all patients circulating serum immunocomplexes were elevated (PEG-IKEM). One patient developed acute uveitis at the onset of the disease, the remainder after 5 and 6 months resp. and in all there was a tendency of a protracted course and relapses resp. In two patients uveitis was diagnosed by an aimed examination by means of a slit lamp at a time when there were not yet any clear signs of affection of the eyes. All patients were subjected to percutaneous renal biopsy which revealed an interstitium with uneven lymphoplasmacytic cellulization with infrequent eosinophil and neutrophil polynuclear cells. Electron microscopy revealed sections of varying size with fibrotization of the tubular basal membrane; the glomerular changes were not typical. All patients had prednisone treatment and their renal functions were gradually restored. Despite extensive serological examinations, the aetiology was not cleared, however before the onset of the disease the patients had penicillin, cotrimoxazol and erythromycin resp.
Keywords: mužské pohlaví; uveitida; ženské pohlaví; akutní nemoc; intersticiální nefritida; Humans; Nephritis, Interstitial; Female; Uveitis; Adolescent; Acute Disease; dítě; lidé; Male; mladiství; Child